Prediction of Weinberg Angle in Discretized Kaluza-Klein Theory - Van Dat, Nguyen (VNU Journal of Science: Mathematics - Physics; Vol 35 No 3DO - 10.25073/2588-1124/vnumap.4350, 2019)
In the discretized Kaluza-Klein theory (DKKT), the gauge fields emerge as components of gravity with a single coupling constant. Therefore, it provides a new approach to fix the parameters of the Standard Model, and in particular the Weinberg angle. The study results show that in the approach using DKKT, the predicted value of Weinberg angle is exactly the one measured in the electron-positron collider experiment at Q = 91.2 GeV/c. The result is compared to the one predicted by the group theoretic methods.